2022
DOI: 10.3390/biom12020276
|View full text |Cite
|
Sign up to set email alerts
|

APR-246—The Mutant TP53 Reactivator—Increases the Effectiveness of Berberine and Modified Berberines to Inhibit the Proliferation of Pancreatic Cancer Cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the most common form of pancreatic cancer. In ~75% of PDAC, the tumor suppressor TP53 gene is mutated. Novel approaches to treat cancer involve compounds called mutant TP53 reactivators. They interact with mutant TP53 proteins and restore some of their growth suppressive properties, but they may also interact with other proteins, e.g., TP63 and TP73. We examined the ability of the TP53 reactivator APR-246 to interact with eleven modified berberine compounds (NAX compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The combination treatment with the NAMPT inhibitor could reduce the p53 R175H aggregative signal to refine the p73 activator effect. A similar combination treatment idea was also used recently to add APR-246 to reactive GoF p53 mutants, to refine the anti-cancer effect of berberine and modified berberine compounds in pancreatic cancer, according to the second approach as mentioned above [53].…”
Section: Discussionmentioning
confidence: 99%
“…The combination treatment with the NAMPT inhibitor could reduce the p53 R175H aggregative signal to refine the p73 activator effect. A similar combination treatment idea was also used recently to add APR-246 to reactive GoF p53 mutants, to refine the anti-cancer effect of berberine and modified berberine compounds in pancreatic cancer, according to the second approach as mentioned above [53].…”
Section: Discussionmentioning
confidence: 99%
“…The role of this drug was investigated in pancreatic cancer cell lines. It was found that APR-246 sensitized MIA-PACA-2 cells to berberine compounds [112]. Further, APR-246 has been investigated in several clinical trials.…”
Section: Targeting Mutant P53mentioning
confidence: 99%
“…Low doses of APR-246 reduced the IC 50 concentrations of chemotherapeutic drugs, signal transduction inhibitors, BBR, or certain NAX compounds [ 203 , 204 ]. The ability of APR-246 to lower the IC 50 s of chemotherapeutic drugs, signal transduction inhibitors, BBR and modified NAX compounds was dependent on the presence of WT-TP53 or GOF mut-TP53 as APR-246 did not lower the IC 50 s of chemotherapeutic drugs, signal transduction inhibitors, berberine or certain NAX compounds in PDAC cells which were TP53-null.…”
Section: Possibility Of Treatment Of Pdac With Small Molecule Signal ...mentioning
confidence: 99%